Size Effects in Nanostructures Basics and Applications - Kuncser, Victor; Miu, Lucica; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
The influence of size effects on the properties of nanostructures is subject of this book. Size and interfacial effects in oxides, semiconductors, magnetic and superconducting nanostructures, from very simple to very complex, are considered. The most general meaning is assumed for size effects, including not only the influence of a reduced dimension/dimensionality, but also specific interfacial effects. Preparation and characterization tools are explained for various nanostructures. The specific applications are discussed with respect to size-related properties. A logic implication of type phenomenon-property-material-application is envisaged throughout this work.
Size effects in semiconductor nanostructures for optoelectronic and photoelectric applications -- Size effects in functional materials for various applications -- Size effects and magnetic behavior.
Keywords: Materials science; Nanoscale science; Nanoscience; Nanostructures; Physics; Nanotechnology; Structural materials; Optical materials; Electronic materials; Materials Science; Optical and Electronic Materials; Nanoscale Science and Technology; Nanotechnology and Microengineering; Applied and Technical Physics; Structural Materials; Nanotechnology; Electronic books